PENGARUH PERMAINAN RODA PUTAR TERHADAP PENGETAHUAN SEKS PADA ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA KECAMATAN BANGKINANG KOTA KABUPATEN KAMPAR - Muhti, Alfiza Yuliana; Novianti, Ria; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the effect of rotate wheel game towards sex knowledge of the children aged 5-6 years old. This research was conducted in TK Negeri Pembina Kecamatan Bangkinang Kota Kabupaten Kampar during April to May 2017. This research is an experimental research using one group pre-test design post-test design through test using child work sheet to child sex knowledge. The population in this study is the whole group B and the sample in this study amounted to 17 children. The method used in pre-experiment with one group design is the experiment conducted on one group only without any comparison group. The type of instrument used in this study is to use the test of sex knowledge in children to know the knowledge of the child during the treatment given. Based on hypothesis test results obtained there is the influence of rotate wheel game towards sex knowledge of the children aged 5-6 years old in TK Negeri Pembina Kecamatan Bangkinang Kota Kabupaten Kampar. Retrieved tcount at 10.549 with sig 0000, because sig <0.05 then we can conclude that there are significant influence rotate wheel game towards sex knowledge of the children. In Hypothesis test can be seen tcount = 10.549> t table = 2.120. It can be interpreted that there is a significant influence rotate wheel game towards sex knowledge of the children aged 5-6 years old is 66.81%.Keywords: Child Sex Knowledge, The Rotate Wheel Game